THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS A MEDIATOR IN THE EFFECT OF WORK PASSION FACTORS ON ORGANIZATIONAL COMMITMENT AMONG TEACHERS IN SELANGOR - Ibrahim, Amalina (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on the effect of work passion factor on organizational commitment among teachers where organizational citizenship behavior (OCB) as a mediator. The first objective of this study is to determine the level of work passion factors, OCB and organizational commitment. Secondly, to determine the effect of work passion factors and OCB on organizational commitment. Thirdly, to determine the effect of work passion factors on OCB, and lastly, to determine the role of OCB as mediator in the effect of work passion factors on organizational commitment among teacher. This is a quantitative study and involved a total of 355 school teachers in Selangor through multi-stage cluster sampling techniques. Data were analyzed through AMOS software to determine the fitness indexes of the structural models. Findings showed work passion factors and organizational commitment among school teachers in moderate level, while OCB at higher level. SEM analysis showed the respecification structural model in this study were significant and achieved fitness indexed (ChiSq/df= 2.51, GFI = 0.97, CFI=0.98, TLI=0.97, RMSEA=0.07). Besides, work passion factors and OCB significantly has a direct effect on organizational commitment. Meanwhile, organizational factors and individual factors were significantly have a direct effect on OCB. Lastly, OCB has a role as a mediator in the effect of organizational factors and individual factors on organizational commitment. The model of this study is appropriate in the context of school teachers in Selangor.